Determinan Kejadian Sibling Rivalry pada Anak Usia Prasekolah: Analisis Pengetahuan Orang Tua dan Pola Asuh - Safria Rustiani Ayuningsih; Frengki Apryanto; Abdul Qodir (STIKES Widyagama Husada, 2026)
Sibling rivalry is a common behavioral phenomenon among preschool-aged children and may negatively affect their emotional and social development if not properly managed. Parental knowledge and parenting style are considered important factors influencing the occurrence of sibling rivalry. This study aimed to analyze the simultaneous relationship between parental knowledge and parenting style with the incidence of sibling rivalry and to identify the most dominant determinant factor among preschool-aged children in Sadang Village, Jatirogo District, Tuban Regency. This study utilized a descriptive analytical with a cross-sectional approach involving 79 respondents selected through random sampling. Data were collected using questionnaires measuring parental knowledge, parenting style, and sibling rivalry, and analyzed using Pearson correlation, Chi-Square and ordinal logistic regression tests. The results showed a significant negative correlation between parental knowledge and sibling rivalry (r = –0.668; p < 0.001) as well as between parenting style and sibling rivalry (p < 0.001). Simultaneous analysis indicated that both parental knowledge and parenting style significantly influenced the incidence of sibling rivalry (p < 0.001). Parental knowledge was identified as the most dominant factor affecting sibling rivalry among preschool children. In conclusion, higher levels of parental knowledge and appropriate parenting styles significantly reduce the incidence of sibling rivalry. Therefore, educational interventions for parents regarding effective parenting practices and understanding sibling rivalry are essential to promote healthy child development and harmonious sibling relationships.